Nietzsche and christianity - Szklarska, Anna (Hybris, 2015)
The article presents connections between philosophy of Nietzsche and the Christian tradition. Author's considerations are not restricted to how Nietzsche assessed Christianity and what he thought of it, but rather: did he reason aptly, did he grasp it correctly. It is a fact that Nietzsche fights with Christianity, which does not prevent him from internalizing some Christian themes in spite of having a very superficial and incomplete picture of it. There are unquestionable differences in both doctrines such as the relationship to the issues of truth, compassion, transcendence, mercy and eternity. Nevertheless they share a large number of common elements: praise for authenticity, creativity and freedom, the ethics of dignity, the postulate of self-formation, appreciation of suffering, rejection of revenge and everything that is small and false, and finally, discipline of the will craving repetition as a confirmation of self, faithfulness to self.